2023
DOI: 10.3390/ph16060783
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB in Cell Deaths, Therapeutic Resistance and Nanotherapy of Tumors: Recent Advances

Abstract: The transcription factor nuclear factor-κB (NF-κB) plays a complicated role in multiple tumors. Mounting evidence demonstrates that NF-κB activation supports tumorigenesis and development by enhancing cell proliferation, invasion, and metastasis, preventing cell death, facilitating angiogenesis, regulating tumor immune microenvironment and metabolism, and inducing therapeutic resistance. Notably, NF-κB functions as a double-edged sword exerting positive or negative influences on cancers. In this review, we sum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 165 publications
0
1
0
Order By: Relevance
“…NF-κB is a transcription factor that plays important roles in cellular functions such as proliferation, differentiation, and apoptosis [75]. Currently, there is substantial evidence pointing to the dual role of NF-κB in cancer [76]. There was a favorable interaction between EZ and NF-κB, with amino acid residues involved in this binding also participating in the interaction between DXR and NF-κB (Cys120, Arg187, and Tyr36).…”
Section: Discussionmentioning
confidence: 99%
“…NF-κB is a transcription factor that plays important roles in cellular functions such as proliferation, differentiation, and apoptosis [75]. Currently, there is substantial evidence pointing to the dual role of NF-κB in cancer [76]. There was a favorable interaction between EZ and NF-κB, with amino acid residues involved in this binding also participating in the interaction between DXR and NF-κB (Cys120, Arg187, and Tyr36).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, it has been verified that CAFs exhibit elevated levels of pro-inflammatory factors and can secrete signaling molecules (e.g., IL-8 and HMGB1) that activate the NF-κB pathway in neighboring cancer cells [ 137 139 ]. Notably, NF-κB activation is intricately related to inflammasome signaling and has the potential to mediate the expression of genes associated with pyroptosis [ 140 , 141 ]. Furthermore, Chalkidi et al analyzed the transcriptomic profile of CAFs in colitis-associated cancer and revealed the significant enrichment pathways in pyroptosis within CAFs [ 142 ].…”
Section: Effects Of Cafs On Tumor Pyroptosismentioning
confidence: 99%